Prevalence and Risk Factors of Intestinal Protozoan Infection in HIV/AIDS Patients in Dr. Sardjito General Hospital Yogyakarta - Ershandi Resnhaleksmana; Elizabeth Sutarti; Mahardika Agus Wijayanti (Pusat Kedokteran Tropis, 2011)
Introduction: Intestinal protozoa is one of the etiology of gastroenteritis in developing countries. The risk of intestinal protozoan infection increases among HIV/AIDS patients. HIV/AIDS patients with CD4+ T cell < 200 cells/μL are easily infected by intestinal protozoa causing broad clinical symptoms including diarrhea and even death. However, it can be prevented by understanding various risk factors which have role in thepathogenesis of intestinal protozoan infection.Objectives: To study the prevalence and risk factors which aff ect intestinal protozoan infection among HIV/AIDS patients in RSUP Dr. Sardjito Yogyakarta.Methods: Data from 32 HIV/AIDS patients in RSUP Dr Sardjito Yogyakarta in December 2009-March 2010 were obtained by questionnaires, medical records, and macroscopic-microscopic examination of fecal samples with phormol-eter method and acid-fast staining. Data was analysed using Chi square test and multivariate analysis. A p value less than 0.05 is considered as a signifi cantly diff erent.Results: Prevalence of intestinal protozoan infection in HIV/AIDS patients in RSUP Dr Sardjito Yogyakarta was 81.2%. Intestinal protozoa found in fecal examination were Cryptosporidium sp. (60.98%), Microsporidiumsp. (19.51%), Entamoeba histolytica (9.76%), Cyclospora cayetanensis (4.88%), Blastocystis hominis (2.44%), and Giardia lamblia (2.44%) (n = 26). Bivariate analysis showed that in female HIV/AIDS patients with clinical stadium 1 and 2, CD4+ T cell ≥ 200 cells/μL, had lower risk to be infected by intestinal protozoa (RR = 0.600, 0.065, and 0.026, respectively). Intestinal protozoa were easily found in feces of HIV/AIDS patients with diarrheal symptom. In multivariate analysis, clinical stadium was the most signifi cant factor (Exp(β) = 18.85).Conclusion: Prevalence of intestinal protozoan infection in HIV/AIDS patients in RSUP Dr Sardjito Yogyakarta in December 2009-March 2010 was 81.2%. Clinical stadium with moderate and severe symptoms was the most dominant risk factor for intestinal protozoan infection in HIV/AIDS patients.Keywords: risk factor, intestinal protozoa, CD4+ T cell - HIV/AIDS patient